KINERJA ORTHOGONAL FREQUENCY DIVISION MULTIPLE ACCESS (OFDMA) PADA TEKNOLOGI RADIO OVER FIBER (ROF) - Rakhmania, Amalia Eka; Pramono, Sholeh Hadi; Kurniawan, Dwi Fadila (Gema Teknologi, 2019)
Amalia Eka Rakhmania, Sholeh Hadi Pramono, Dwi Fadila Kurniawan, in this paper explain that radio over Fiber (RoF) is a technology that integrates wireless and wireline transmission system to transmit radio signal through optical fibre cable. This paper evaluates the performance of Orthogonal Frequency Division Multiple Access (OFDMA) implemented in RoF system for mobile WiMAX network. RoF channel model includes both optical fiber with Relative Intensity Noise, shot noise, thermal noise, and chromatic dispersion, and also wireless channel with Additive White Gaussian Noise (AWGN). Through simulation, signal to noise ratio (SNR), channel capacity, bit rate, and bit error rate (BER) with the influence of optical fiber length and wavelength. Result shows that optical fiber length is proportional to SNR, channel capacity, and bit rate but inversely proportional to BER. 1550 nm wavelength has better channel capacity but lesser bit rate than 1310 nm.